2021
DOI: 10.7554/elife.67510
|View full text |Cite
|
Sign up to set email alerts
|

A developmental framework linking neurogenesis and circuit formation in the Drosophila CNS

Abstract: The mechanisms specifying neuronal diversity are well-characterized, yet it remains unclear how or if these mechanisms regulate neural circuit assembly. To address this, we mapped the developmental origin of 160 interneurons from seven bilateral neural progenitors (neuroblasts), and identify them in a synapse-scale TEM reconstruction of the Drosophila larval CNS. We find that lineages concurrently build the sensory and motor neuropils by generating sensory and motor hemilineages in a Notch-dependent manner. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 57 publications
(103 reference statements)
7
72
0
Order By: Relevance
“…The diversity of dopamine neuron activity challenges models of mushroom body learning that assume these neurons convey global reward or punishment signals. Part of this discrepancy is likely due to the intricate connectivity among output neurons, dopamine neurons, and other neurons that form synapses with them [ 48 , 52 , 53 ]. We therefore modeled these neurons and their connections, which we refer to collectively as the mushroom body “output circuitry,” as a recurrent neural network ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diversity of dopamine neuron activity challenges models of mushroom body learning that assume these neurons convey global reward or punishment signals. Part of this discrepancy is likely due to the intricate connectivity among output neurons, dopamine neurons, and other neurons that form synapses with them [ 48 , 52 , 53 ]. We therefore modeled these neurons and their connections, which we refer to collectively as the mushroom body “output circuitry,” as a recurrent neural network ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of an explicit correspondence between neurons in our model and their biological counterparts, direct analysis of the connectivity in our optimized networks is unlikely to be sufficient to do so. Future studies should build models that incorporate recently available mushroom body wiring diagrams to further constrain models [ 49 , 50 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), which is specified by temporal transcription factor expression in neuroblasts (Isshiki et al, 2001). It has been suggested that these genetic mechanisms specifying neuronal diversity are also likely to govern circuit formation and function (Mark et al, 2021) (Sagner & Briscoe, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These data linked temporal cohorts to differential circuit function. More recently, in other lineages (i.e., NB1-2, NB2-1, NB3-1, NB4-1, NB5-2, NB7-1, NB 7-4), neurons within temporal cohorts were shown to share similarities in their synaptic partnerships (Meng et al, 2019) (Meng et al, 2020) (Mark et al, 2021). Furthermore, the number of neurons in lineage that are segregated into a given temporal cohorts can be altered by manipulating temporal factor expression in neuronal stem cells (Meng et al, 2019) (Meng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%